Precursor forms of Vitamin D reduce HIV-1 infection in vitro (2016)
ABSTRACT: Background: Although the anti-HIV-1 effects of vitamin D (VitD) have been reported, mechanisms behind such protection remain largely unexplored. Methods: The effects of two precursor forms (cholecalciferol/calciol at 0.01, 1 and 100 nM and calcidiol at 100 and 250 nM) on HIV-1 infection, immune activation, and gene expression were analyzed in vitro in cells of Colombian and Italian healthy donors. We quantified levels of released p24 by enzyme-linked immunosorbent assay, of intracellular p24 and cell-surface expression of CD38 and HLA-DR by flow cytometry, and mRNA expression of antiviral and immunoregulatory genes by real-time reverse transcription-polymerase chain reaction. Results: Cholecalciferol decreased the frequency of HIV-1-infected p24CD4 T cells and levels of p24 in supernatants in a dose-dependent manner. Moreover, the CD4CD38HLA-DR and CD4CD38HLA-DR subpopulations were more susceptible to infection but displayed the greatest cholecalciferol-induced decreases in infection rate by an X4-tropic strain. Likewise, cholecalciferol at its highest concentration decreased the frequency of CD38HLA-DR but not of CD38HLA-DR T-cell subsets. Analyzing the effects of calcidiol, the main VitD source for immune cells and an R5-tropic strain as the most frequently transmitted virus, a reduction in HIV-1 productive infection was also observed. In addition, an increase in mRNA expression of APOBEC3G and PI3 and a reduction of TRIM22 and CCR5 expression, this latter positively correlated with p24 levels, was noted. Conclusions: VitD reduces HIV-1 infection in T cells possibly by inducing antiviral gene expression, reducing the viral co-receptor CCR5 and, at least at the highest cholecalciferol concentration, by promoting an HIV-1-restrictive CD38HLA-DR immunophenotype.